Tri-axial Time-frequency Analysis for Tool Failures Detection in Deep Twist Drilling Process - M. H. S., Harun; M. F., Ghazali; A. R., Yusoff (Elsevier, 2016)
Premature tool failure in deep drilling reduces product quality. By analyzing the deep drilling process signals through time and frequency domains in tri-axial vibrations, the early conditions before tool failure can be detected. From the experimental data, vibration time domain signals were analyzed by short-time Fourier transform to detect the tool wear mechanism. Results showed that tool wear accelerated before failure as increasing feed rate and cutting speed were recognized in the y- and z-axes in time–frequency analysis.